Economic Transactions In Islamic Financial Institutions: Analysis of Fiqh Rules, Opportunities, and Challenges in The Era Of Globalization - Harahap, Alfi Andriansyah; Imsar, Imsar (Al-Fikru: Jurnal Ilmiah, 2023)
The presence of fiqh rules is a solution in responding to problems related to the determination of Islamic law in facing the realities of today. Especially, in the context of transactions in Islamic financial institutions, fiqh rules play an important role in determining the law in accordance with the teachings of the Qur'an, Hadith, and Ijma. The rules of fiqh are present with the main purpose of determining Islamic law in the face of new challenges that continue to develop along with the changing times, especially in the context of economic transactions or muamalah maliyah which continues to grow in Islamic financial institutions. The rules of fiqh are the result of ijtihad and are a generalization of various fiqh themes that have spread among the scholars of the madhhab. The presence of these rules is very important to provide a framework that makes it easy to determine contemporary laws, especially related to economic issues that often do not have nash sharîh (definite evidence) in the Qur'an or Hadith. Thus, the rules of fiqh become a much-needed instrument in providing understanding and resolution of legal issues that arise in the context of modern economics, especially in Islamic financial institutions